Identifying Vegetation Dynamics and Sensitivities in Response to Water Resources Management in the Heihe River Basin in China - Dongqin Yin; Xiang Li; Yuefei Huang; Yuan Si; Rui Bai (Advances in Meteorology)
The Heihe River Basin, the second largest inland river basin in China, plays a vital role in the ecological sustainability of the Hexi Corridor. However, the requirements for regional economic development and ecological balance cannot be fully met due to water resource shortage and overexploitation induced by an extremely dry climate and population growth, especially in the middle and lower basins. Thus, environmental conservation projects that reallocate water resources have been planned and implemented step by step since 2001. The aim of this study is to evaluate ecosystem restoration benefits by identifying vegetation dynamics and sensitivities. The MODIS Normalized Difference Vegetation Index (NDVI) and its derivative indices, coupled with Geographic Information System (GIS), are introduced to explore ecosystem evolution at the pixel level, based on the hydrological and meteorological data in the whole region at varying temporal and spatial scales. Results indicate there are slight vegetation restoration trends in the upper, middle, and lower basin; the results of correlation analyses between vegetation and runoff into the lower basin suggest that the impact of a water supplement lasts at most three years, and engineering or nonengineering measures should be maintained for permanent ecosystem recovery.